If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + -5x = 13 Combine like terms: 6x + -5x = 1x 1x = 13 Solving 1x = 13 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Divide each side by '1'. x = 13 Simplifying x = 13
| 6-5x+8+3x+3x-2=9+2.4 | | K=37+273 | | 5p-14-8p=4 | | 2y-3=3y | | 2c^3+16c^2-18c=0 | | (x-3)=-2 | | 20x^3-20x=0 | | 4(6x+2)=56 | | 3x-4=4x-17 | | k^2-3k+5=0 | | 4y-7=2(y+1) | | F=1.8(37)+32 | | 5y-20=10 | | 12x^5+15x+9=0 | | -x^2+15x+54=0 | | K=10+273 | | 2x+6=-26-6x | | 4y-1=2y+2 | | X^2=3(5x+18) | | 5x+5-2x=29 | | 9+6x=x+59 | | (3x-2)(x-2)=4x-36 | | 20y-16=18-9 | | K=40+273 | | 4(3a-2)+3a=19 | | F=1.8(40)+32 | | 7x-10=114-6x | | 305=5x^3 | | K=30+273 | | -6+7x=x-12 | | 3(2x+5)=11-4x | | 6y(4y-3)+15y= |